2008
DOI: 10.1007/s12040-008-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of temperature on tropospheric ozone concentration levels in urban environments

Abstract: The influence of temperature on tropospheric ozone (O 3 ) concentrations in urban and photochemically polluted areas in the greater Athens region are investigated in the present study. Hourly values of the ambient air temperature used for studying the urban heat island effect in Athens were recorded at twenty-three experimental stations while ozone concentration values were measured at three of the above-mentioned stations and for a period of two years (1996)(1997). The linear correlation between ozone concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(89 citation statements)
references
References 51 publications
4
73
1
11
Order By: Relevance
“…In this paper we show significant correlations between O 3 levels and meteorological conditions, positive with radiation, air temperature, wind velocity, while negative with air humidity, and negative or positive with atmospheric pressure, which is similar to the findings of Liu et al [10], Aref'ev et al [14], Stathopoulou et al [17], Adame et al [37], Puc and Bosiacka [39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this paper we show significant correlations between O 3 levels and meteorological conditions, positive with radiation, air temperature, wind velocity, while negative with air humidity, and negative or positive with atmospheric pressure, which is similar to the findings of Liu et al [10], Aref'ev et al [14], Stathopoulou et al [17], Adame et al [37], Puc and Bosiacka [39].…”
Section: Discussionsupporting
confidence: 90%
“…In urban areas air flow may be disrupted and so the levels recorded at a given station may not reflect the movement of air masses in a larger spatial scale. O 3 flows into Poland with air masses often coming from southern and south-western Europe [17][18][19]; apart from the wind, other meteorological conditions also significantly influence O 3 levels, especially solar radiation, temperature and humidity [20]. O 3 concentration also depends on other factors, such as terrain, altitude and geographic location [21].…”
Section: Introductionmentioning
confidence: 99%
“…For NEM, PC1 (52.6% of the total variance) was loaded with windspeed, relative and humidity and O 3 which grouped all the meteorological factors in one. O 3 has shown a strong correlation with the meteorological factors [28][29][30][31][32][33][34][35] and thus, falls into the same group. The relative humidity shows a negative score which indicates increasing relative humidity brings negative contributions towards PM 10 concentration as high water vapor content in the air provides washing effects which reduce the amount of particles in the atmosphere [36][37].…”
Section: Pincipal Component Analysis Of Particulate Matter Concentrationmentioning
confidence: 99%
“…Among the air pollutants, studies in urban areas have been focused on ozone, due to its strong oxidant property and potential damage to humans once the concentration is increased [137]. Using data from 23 experimental stations, Stathopoulou et al [12] concluded that ambient air temperature is the predominant parameter in affecting the ozone concentration. Among the researchers, Taha is the one that has pioneered most of the studies in this field.…”
Section: Impact Of Reflective Materials On Air Qualitymentioning
confidence: 99%
“…While a significant spatial and temporal variation is observed in the UHI intensity, many cities show a magnitude of 5-11 o C by mid-morning [4]. Elevated environmental temperatures in urban areas lead to rise of energy consumption for cooling [5][6][7][8], increase of peak electricity demand [9], degradation of air quality [10][11][12][13], and deterioration of thermal stress on residents [14,15]. In particular, UHI 6 temperature, if not negligible [21,53].…”
Section: Introductionmentioning
confidence: 99%